A study on the minimum optimal salinity levels for the larval rearing of giant freshwater prawn, Macrobrachium rosenbergii (de Man, 1879) larvae - Mohd Mukriz, Mohd Kasim (Institut Akuakultur Tropika, 2011)
This study was carried out to determine the best minimum optimal salinity, survival rate and metamorphosis rate of the larvae rearing of Giant Freshwater Prawn, M. rosenbergii in different water salinity level, i.e., 3ppt, 6ppt, 9ppt and 12 ppt .The results showed that the larvae took 25-26 days to reach porstlarvae in tank treated with salinity 3ppt, 27-29 days in water salinity 6 and 9ppt, while it took 31-33 days for larvae to reach postlarvae in tank treated with water salinity 12ppt. The metamorphosis rate showed that there were no significant differences from all the treatments. The number of day to reach larvae stage IV for all water salinity is almost similar which takes 7 - 1 4 day to reach stage IV. However, the next stage shows that larvae in water salinity 3ppt have a faster metamorphosis rate compare to larvae in higher salinity.